The Students’ Comprehension in Identifying Suffix –ing As An Inflection and A Derivation - Giyatmi - Giyatmi; Sihindun - Arumi (Universitas Muhammadiyah Tangerang, 2024)
The research aims at describing the students’ comprehension on identifying suffix -ing as an inflection or a derivation. This is a descriptive qualitative research. The populations are 12 students of the 6th semester of English Department. The students’ score taken by test are used as the data. The writers analyzed the students' test results to determine the students' comprehension on -ing suffix. Based on the analysis, the students’ comprehension on suffix -ing as a derivation and inflection belongs to sufficient category (72,2). Furthermore, the writer found that the students' inability to grasp the function and role of each part of speech in English grammar lead the students to misidentify suffix –ing as an inflection or a derivation.